2012
DOI: 10.1016/j.vph.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reverses monocrotaline-induced pulmonary vascular and cardiac dysfunction: A potential role for atrogin-1 in smooth muscle

Abstract: Arterial remodeling contributes to the elevated pulmonary artery (PA) pressures and right ventricular hypertrophy seen in pulmonary hypertension (PH). Resveratrol, a sirtuin-1 (SIRT1) pathway activator, can prevent the development of PH in a commonly used animal model, but it is unclear whether it can reverse established PH pathophysiology. Furthermore, atrophic ubiquitin ligases, such as atrogin-1 and MuRF-1, are known to be induced by SIRT1 activators but have not been characterized in hypertrophic vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 43 publications
6
55
0
Order By: Relevance
“…Currently, several studies have documented that Rev possesses various biological properties, including antioxidant, anti-inflammatory, and anti-proliferative properties, and promotes cell differentiation and apoptosis [27-30]. The data from a recent study showed that Rev reversed the remodelling of the pulmonary vasculature by restoring atrophic gene expression in MCT-induced PH [18]. In addition, Zhou et al showed that Rev could elevate the activation of SIRT1 and p21 but decreased cyclin D1 expression in MCT-induced PAH [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several studies have documented that Rev possesses various biological properties, including antioxidant, anti-inflammatory, and anti-proliferative properties, and promotes cell differentiation and apoptosis [27-30]. The data from a recent study showed that Rev reversed the remodelling of the pulmonary vasculature by restoring atrophic gene expression in MCT-induced PH [18]. In addition, Zhou et al showed that Rev could elevate the activation of SIRT1 and p21 but decreased cyclin D1 expression in MCT-induced PAH [19].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (Rev, 3,5,4-trihydroxystilbene), a polyphenol isolated from grapes and polygonum cuspidatum, has been shown to possess antioxidative properties [17]. A recent study showed that Rev could reverse monocrotaline-induced pulmonary vascular remodelling and prevent the progression of PAH [18, 19]. However, the exact anti-PAH function of Rev has not been fully uncovered until now.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SIRT1 has come to the attention of researchers in the field, as it may protect against lung inflammation and PASMC proliferation. 4648 Resveratrol, a SIRT1 activator, has been shown to prevent or rescue MCT-induced PAH in rats by reducing inflammation and oxidative stress and inhibiting PASMC proliferation. 4648 Inhibition of SIRT1 increased SMC proliferation 48 , while resveratrol prevented SMC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, resveratrol improved endothelial function, attenuated inflammation and oxidative stress, and inhibited proliferation of pulmonary artery smooth muscle cells [70]. In addition, resveratrol has also been shown to reverse established pulmonary hypertension when it was administered 28 days after the monocrotaline injection [71,72]. In a model of pulmonary thromboembolisminduced pulmonary hypertension, two doses of resveratrol (10 mg/kg; IP) significantly reduced mean pulmonary artery pressure through down-regulation of monocyte chemo-attractant protein-1 (MCP-1), and P-p38 mitogen-activated protein kinase (MAPK) [73].…”
Section: Accepted Manuscriptmentioning
confidence: 98%